Possibilities of Terms in the Literary Text - Alimova Namuna Numanovna (Research Parks Publishers, 2022)
The article examines in terms of the text the transformation of terms in a work of art into a means of expressing art in connection with the idiolect of the writer. The use of terms in a single sense and their inability to perform an aesthetic function has been advanced in the scientific literature. In the article, the introduction of vertical and horizontal relations of terms in a work of art is interpreted in the example of the works of Askad Mukhtor.